2018
DOI: 10.15294/jejak.v11i2.16048
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Health in Local Government Based on Soft System

Abstract: The purpose of this paper is to identify problems and construct a conceptual model related to the local fiscal health condition. The local fiscal health condition is highly dependent on many factors, indicating that local finance is a complex, systemic and unstructured process. The main emphasis in this research is that the researchers attempt to explore the problem situation with the interpretive and naturalistic approach toward the local fiscal health condition and to study, understand, and interpret the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…Dengan demikian, pemerintah daerah harus menjaga kesehatan keuangan agar krisis keuangan tidak terjadi di masa depan. Pengelolaan keuangan pemeirntah daerah yang baik mendorong pemerintah daerah tersebut tetap menjaga kesehatan keuangannya (Suryawati et al, 2018). Dengan demikian, pemerintah daerah mampu untuk mengelola sumber daya keuangannya dengan baik (Suryawati et al, 2018).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Dengan demikian, pemerintah daerah harus menjaga kesehatan keuangan agar krisis keuangan tidak terjadi di masa depan. Pengelolaan keuangan pemeirntah daerah yang baik mendorong pemerintah daerah tersebut tetap menjaga kesehatan keuangannya (Suryawati et al, 2018). Dengan demikian, pemerintah daerah mampu untuk mengelola sumber daya keuangannya dengan baik (Suryawati et al, 2018).…”
Section: Pendahuluanunclassified
“…Pengelolaan keuangan pemeirntah daerah yang baik mendorong pemerintah daerah tersebut tetap menjaga kesehatan keuangannya (Suryawati et al, 2018). Dengan demikian, pemerintah daerah mampu untuk mengelola sumber daya keuangannya dengan baik (Suryawati et al, 2018). Kemampuan pemerintah daerah dalam mengelola sumber daya keuangan dapat menjadi indikator bahwa pemerintah daerah memiliki kualitas laporan keuangan yang baik.…”
Section: Pendahuluanunclassified
“…The social work profession has utilized technology in such a way that the field has undergone many changes in the education and training of social workers as well as the ways in which services can be provided to clients. Meanwhile, Suryaweti et al [5] identified problems and built a conceptual model related to local fiscal health conditions in a local government in Bondowoso district, East Java Province. The state of the fiscal health of the region is highly dependent on many factors, indicating that regional finance is a complex, systemic and unstructured process.…”
Section: Introductionmentioning
confidence: 99%